Assessment of competencies of clinical research professionals and proposals to improve clinical research in Portugal - Bogas, Mónica; Antas, Joana; Magalhães, Cátia; Revige, Mafalda; Guerra, Liliana; Ribeiro, Cheila; Eça, Rita Cunha; Nunes, Filipa; Lopes, Ana; Costa, Luís; Gonçalves, Mónica; Pedrosa, Jorge; et al. (Frontiers in Pharmacology, 2025)
BackgroundClinical studies are coordinated by multidisciplinary teams, which often lack adequate training and competencies. In this study, ROCHE and AICIB (Agency for Clinical Research and Biomedical Innovation) conducted a self-assessment survey aiming to evaluate the competency of clinical research professionals to conduct clinical research in Portugal and promote the identification of key actions to address priority gaps.MethodsClinical research professionals from 10 Portuguese centres answered an electronic survey, adapted and translated from the Joint Task Force for Clinical Trial Competency (JTFCTC) framework. Representatives of the centres, ROCHE and AICIB held a meeting to discuss the survey results, identify priority gaps and propose recommendations.ResultsA total of 109 participants answered the questionnaire with the following national geographical distribution: North (n = 46), Centre Region (n = 16), and Lisbon metropolitan area (n = 47). A considerable proportion were Investigators (44.0%) and had more than 10 years of experience (34.9%). The eight JTFCTC Domains scored under 60% in the level of knowledge, with Investigators achieving overall higher scores. To address these gaps, key actions were proposed, such as enhancing training and educational opportunities, fostering collaboration and networking, and investing in infrastructure and resources.ConclusionThis study was the first to assess clinical trial competency in Portugal, registering a high participation rate. The study highlights the need to develop a national plan of action, in a collaborative effort, between clinical research centres, universities, industry, regulatory authorities, national agencies, and patient organizations. This will not only contribute to elevate the quality of studies but also improve compliance with international standards, ultimately benefiting both researchers and patients.